Development of Project-Based Learning Integrated with Local Culture to Enhance Critical Thinking Skills of Students in Fine Motor Skills Development Course - Sari, Dwi Lyna; Agustriana, Nesna; D, Delrefi; Retnaningsih, Lina Eka (Universitas Islam Lamongan, 2024)
Students interest in local culture tends to decline, especially in the face of globalization's influence, which shifts cultural values. This study aims to develop a Project-Based Learning (PjBL) model integrated with local culture to enhance students' critical thinking skills in the course on the Development of Fine Motor Skills. This research is a development study or Research and Development (R&D) utilizing the 4D model (Define, Design, Development, and Dissemination). The research sample consists of third-semester students from the Early Childhood Education Teacher Program at Universitas Bengkulu for the 2024/2025 academic year. Data collection is conducted through interviews, observations, questionnaires, and documentation, while data analysis employs qualitative analysis methods. The results indicate that the local culture-based PjBL model meets the criteria of being valid, practical, and effective in improving students' critical thinking skills. This effectiveness is demonstrated through a three-phase trial showing significant differences in students' abilities before and after the implementation of PjBL. Future researchers are encouraged to implement the local culture-based PjBL model more broadly across various study programs and courses, as well as conduct further research to evaluate the long-term impact of PjBL implementation on the development of critical thinking skills and other learning aspects